Affordability of in vivo gene therapy. Problems and potential solutions - V. V. Omelyanovskiy; N. Z. Musina; V. A. Lemeshko; A. A. Antonov; F. V. Gorkavenko (IRBIS LLC, 2020)
Aim. To review foreign approaches to the evaluation and financing of in vivo gene therapy drugs.Materials and Methods. The first stage of the review included the systematic search for publications of clinical-economic studies (CES) on in vivo gene therapy drugs registered on the international pharmaceutical market. The analysis of the methodology used in the found CESs was performed based on the given criteria. The second and third stages of the review included the search for the information on the approaches and results of the evaluation of in vivo gene therapy drugs by foreign agencies on the assessment of healthcare technologies (AHT) and the implemented approaches to the financing of expensive medical technologies.Results. Totally, four in vivo gene therapy drugs registered on the foreign markets were found: talimogene laherparepvec (Imlygic), voretigene neparvovec (Luxturna), onasemnogene abeparvovec (Zolgensma), and alipogene tiparvove (Glybera). The analysis of the methodology of CES on in vivo gene therapy drugs did not reveal general methodological peculiarities. The analysis of the approaches to the reimbursement for the cost of these four drugs in the European countries showed that there were no special procedures intended for gene drugs. However, in the majority of countries, there are some mechanisms of reimbursement for orphan drugs and the majority of the above-mentioned in vivo gene therapy drugs are orphan. It was revealed that the most perspective methods of payment for in vivo gene therapy drugs were installment payments, risk-sharing agreements, and their combinations. Still, none of these payment methods are implemented in Russia because of the lack of regulatory and legal framework.Conclusion. The design and methodological peculiarities of CES on in vivo gene therapy drugs are similar to orphan drugs (in some countries, there is a special flexible procedure). In the Russian Federation, there is no special procedure of ATH for orphan drugs, which can provide difficulties in the reimbursement for these drugs. Besides, in the Russian Federation, the issue of the implementation of innovative models for drugs provision (risk-sharing, installment payments is acute). The changes in this area would also lead to the optimization of the influence of expensive healthcare technologies on the budget of the system of healthcare.